SKIN REACTIONS DUE TO THE USE OF PERSONAL PROTECTIVE EQUIPMENT ON HEALTHCARE WORKERS IN COVID-19 PANDEMIC: AT ABDUL WAHAB SYAHRANIE HOSPITAL, SAMARINDA - Mariyati, Ratna Noor; Toruan, Vera Madonna Lumban; Hutahaean, Yetty; Sihotang, Fransiska; Kartini, Agnes (Jurnal Ilmu Kesehatan, 2022)
Since coronavirus disease (Covid-19) cases discovered and became a global problem around the world, healthcare workers (HCWs) are the most frequently confronted with covid patient. The number of cases in Indonesia is quite high, including in Samarinda. Because this virus is very easily transmitted, the use of appropriate Personal Protective Equipment (PPE) on all healthcare workers when carrying out their duties is a must. This applies not only to healthcare workers on duty at covid treatment centers, but also to all health agencies. Face masks, faceshields, medical gloves, coveralls are the types of PPE which used for a long enough duration, can cause unwanted reactions on the wearer's skin. If this reaction is very disturbing and ongoing, it can affect the compliance or influnce their quality of life. The purpose of this study is to determine the diversity of skin disorders that occur to healthcare workers related to the use of PPE, the types of PPE that can cause skin disorders, the relationship between the duration of PPE used and the incidence of skin disorders. The results of this study can later be used as a basis for recommendations of preventive measures for skin reactions. This research is an analytical descriptive study, taking data onto cross section using a questionnaire. The respondents of the study were healthcare workers that served for health institutions in the Samarinda region.